2017
DOI: 10.4236/aim.2017.76041
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Water Quality and Microbial Load of Dhaleshwari River Tangail, Bangladesh

Abstract: The present study was undertaken to investigate some water quality parameters (pH, BOD, DO and water temperature), anion concentration ( 524to the users of the river water but also poses risks for the aquatic organisms especially fish of the water bodies. So the occurrence of high bacterial load concluded that the water of Dhaleshwari river is polluted and unhygienic for drinking and even unsuitable for domestic purposes without proper treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 11 publications
2
20
0
Order By: Relevance
“…The observation of Swingle [26] suggested that pH range 6.5 to 9.0 is suitable for fish culture. The value of pH in the present experiment was suitable for fish culture which was agreed with the findings of Real et al [27] and Rumpa et al [28].…”
Section: Water Quality Parameterssupporting
confidence: 93%
“…The observation of Swingle [26] suggested that pH range 6.5 to 9.0 is suitable for fish culture. The value of pH in the present experiment was suitable for fish culture which was agreed with the findings of Real et al [27] and Rumpa et al [28].…”
Section: Water Quality Parameterssupporting
confidence: 93%
“…Opening of the drain into water sources and direct fecal contamination through opening of latrine indirectly polluted the water (Table 2) (Table 3) [44]. The decrease trend (r = −0.707; p < 0.05) in total coliform bacteria with the increase of DO and increase trend with the increase of temperature (r = 0.755; p < 0.05) [19] which is similar to our study result. One-way ANOVA study was conducted to know the mean differences of the quantity of parameters among different times of sampling (Table 4).…”
Section: Correlation Matrix Among Bacteriological and Physiochemical supporting
confidence: 80%
“…Total coliforms which are used to evaluate the general quality of water, exceeded the WHO recommended acceptable limit in all of our study sample [32]. The range of total coliforms in all of collected samples was varied from cfu/100ml during April in Dhaleshwari River, Tangail [19].…”
Section: Total Coliform Countmentioning
confidence: 99%
“…The pH of the natural water varies between 7 and 8 and the DO ranges between 3 and 5 mg/L. The conductivity of the waters is 1,158 μS/cm, much higher than the reference value for natural waters ( 30 ). The turbidity of the water is 1.1 NTU.…”
Section: Theoretical Composition Of Biofilm Inside the Wasa Water Supmentioning
confidence: 80%
“…If we summarize the parameters reported from independent original studies, we can set the parameters of the supply water within the reported ranges. The temperature of the water in summer is around 30°C ( 30 ). The pH of the natural water varies between 7 and 8 and the DO ranges between 3 and 5 mg/L.…”
Section: Theoretical Composition Of Biofilm Inside the Wasa Water Supmentioning
confidence: 99%